Wow! Great question.
Read in chunks. Stem is hard to understand but the que is too easy.
(
the product of the factors of)
twice the sum of the
roots of the equation \(2x^2 - 4x - 6 = 0\)
\(x^2 - 2x - 3 = 0\)
Roots are : \(3\) & \(-1\)
Sum of roots : \(2\)
Twice the sum of roots : \(4\)
We are asked the product of factors oftwice the sum of roots.
So product of factors of \(4\)
Factors of \(4\) : \(1 , 2 , 4\)
Product = \(1 * 2 * 4 =\) \(8\)
void wrote:
after getting root of equation' what to do?
i lost in sentence ,.....
Posted from my mobile device